Effects of plant essential oils and biocontrol agents on the growth of and mycotoxin production by Aspergillus spp. on groundnut - Alamene, Azawei (2015)
Groundnut, Arachis hypogaea (L.), can be attacked by a range of pathogens, including Aspergillus species, which can cause accumulation of the mycotoxin aflatoxin. Although some success in controlling this pathogen has been achieved with application of fungicides, their use is not always feasible in developing nations like Nigeria. The aim of this study was, therefore, to evaluate naturally-occurring plant oils and BCAs with a past history of efficacy as alternatives to fungicides for reduction of Aspergillus infection and aflatoxin accumulation in groundnut. Aspergillus strains and thirteen different plant essential oils were tested. The oils were derived from clove, camphor, vanilla, garlic, galangal, green oregano, lemon grass, neem, ginger, basil, tea tree, thyme and onion. The biocontrol agents used were fungi Trichoderma harzianum strain T-22, T. asperellum and T. viride from a commercial biocontrol product, TUSAL, and bacteria Pseudomonas chlororaphis ssp. aureofaciens and Bacillus amyloliquefaciens (strains MBI600, 62P, and 66P). The identities of a strain of A. niger, isolated from Nigerian groundnut samples, and of T. asperellum and T. viride were confirmed by PCR amplification of DNA and sequence comparison to reference isolates in the GenBank database. Some of the plant oils (clove, camphor and vanilla) and biocontrol agents (Trichoderma strains) tested proved effective in inhibiting the A. flavus and A. niger strains used in the research, in both in vitro and in planta experiments. Improved seedling emergence in pathogen-contaminated compost and reduced post-harvest pod infection were observed. Combinations of the most active BCAs and EOs also provided disease suppression. ELISA analysis of aflatoxin B1 in treated, A. flavus-inoculated groundnut pods showed a reduction in toxin concentrations, to a level below that recommended by the European Commission of 15 ppb. Of the control agents tested, the most effective were T. harzianum T-22 as a BCA and probably clove oil as a plant extract. Commercial products based on Trichoderma are used world-wide. EOs, have, to date, had little use in control of Aspergillus infection of groundnut. It was also demonstrated that detection of asymptomatic A. flavus pod infection could be achieved by the traditional method of surface sterilisation and plating out, and by use of a LAMP assay to detect pathogen DNA. The latter could provide a rapid, portable method for A. flavus detection in harvested groundnut pods and could have application in both developed and developing nations. Since low resource growers in nations like Nigeria need alternative, low-cost methods for protecting groundnut from Aspergillus infection, to produce a nutritionally-valuable, high protein foodstuff low in toxin contamination, such alternative methods of disease control may have a future role to play in global food security. It may prove possible to extract antifungal components from appropriate, locally-sourced plant material in a cost-effective manner. However, whether the level of disease control and suppression of aflatoxin accumulation reported here was adequate for possible commercial application is unclear. Further evaluation, including field experiments, is required.